Δ9-tetrahydrocannabinol reverses TNFα-induced increase in airway epithelial cell permeability through CB2 receptors - Shang, Valerie C.M.; Kendall, David A.; Roberts, Richard E. (Elsevier, 2016)
Despite pharmacological treatment, bronchial hyperresponsiveness continues to deteriorate as airway remodelling persists in airway inflammation. Previous studies have demonstrated that the phytocannabinoid Δ9-tetrahydrocannabinol (THC)reverses bronchoconstriction with an anti-inflammatory action. The aim of this study was to investigate the effects of THC on bronchial epithelial cell permeability after exposure to the pro-inflammatory cytokine, TNFα. Calu-3 bronchial epithelial cells were cultured at air-liquid interface. Changes in epithelial permeability were measured using transepithelial electrical resistance(TEER), then confirmed with a paracellular permeability assay and expression of tight junction proteins by Western blotting.Treatment with THC prevented the TNFα-induced decrease in TEER and increase in paracellular permeability. Cannabinoid CB1 and CB2 receptor-like immunoreactivity was found in Calu-3 cells. Subsequent experiments revealed that pharmacological blockade of CB2, but not CB1 receptor inhibited the THC effect. Selective stimulation of CB2 receptors displayed a similar effect to that of THC. TNFα decreased expression of the tight junction proteins occludin and ZO-1, which was prevented by pre-incubation with THC.These data indicate that THC prevents cytokine-induced increase in airway epithelial permeability through CB2 receptor activation. This highlights that THC, or other cannabinoid receptor ligands, could be beneficial in the prevention of inflammation induced changes in airway epithelial cell permeability, an important feature of airways diseases.